Plasma neurofilament light as a potential biomarker of neurodegeneration in Alzheimer's disease - Lewczuk, Piotr; Ermann, Natalia; Andreasson, Ulf; Schultheis, Christian; Podhorna, Jana; Spitzer, Philipp; Maler, Juan Manuel; Kornhuber, Johannes; Blennow, Kaj; Zetterberg, Henrik (Alzheimer's Research and Therapy, 2018)
BACKGROUND: A growing body of evidence suggests that the plasma concentration of the neurofilament light chain (NfL) might be considered a plasma biomarker for the screening of neurodegeneration in Alzheimer's disease (AD). METHODS: With a single molecule array method (Simoa, Quanterix), plasma NfL concentrations were measured in 99 subjects with AD at the stage of mild cognitive impairment (MCI-AD; n = 25) or at the stage of early dementia (ADD; n = 33), and in nondemented controls (n = 41); in all patients, the clinical diagnoses were in accordance with the results of the four core cerebrospinal fluid (CSF) biomarkers (amyloid β (Aβ)1-42, Aβ42/40, Tau, and pTau181), interpreted according to the Erlangen Score algorithm. The influence of preanalytical storage procedures on the NfL in plasma was tested on samples exposed to six different conditions. RESULTS: NfL concentrations significantly increased in the samples exposed to more than one freezing/thawing cycle, and in those stored for 5 days at room temperature or at 4 °C. Compared with the control group of nondemented subjects (22.0 ± 12.4 pg/mL), the unadjusted plasma NfL concentration was highly significantly higher in the MCI-AD group (38.1 ± 15.9 pg/mL, p < 0.005) and even further elevated in the ADD group (49.1 ± 28.4 pg/mL; p < 0.001). A significant association between NfL and age (ρ = 0.65, p < 0.001) was observed; after correcting for age, the difference in NfL concentrations between AD and controls remained significant (p = 0.044). At the cutoff value of 25.7 pg/mL, unconditional sensitivity, specificity, and accuracy were 0.84, 0.78, and 0.82, respectively. Unadjusted correlation between plasma NfL and Mini Mental State Examination (MMSE) across all patients was moderate but significant (r = -0.49, p < 0.001). We observed an overall significant correlation between plasma NfL and the CSF biomarkers, but this correlation was not observed within the diagnostic groups. CONCLUSIONS: This study confirms increased concentrations of plasma NfL in patients with Alzheimer's disease compared with nondemented controls.
EVALuna2:211625